In-Situ Loading Test in Deep Soft Soil and Back Analysis Based on Machine Learning Method - Liu, Zhicheng; Zhang, Wengang; Zhang, Xiaoguang (International journal of civil engineering (Tehran. Online), 2025)
To investigate the effects of overlying surcharge on ground deformation in soft soil areas, in-situ loading tests are conducted to monitor soil behavior. Monitoring data, including surface settlement, lateral displacement, stratified settlement, and pore water pressure, are collected from 5th January to 22nd February. The three-dimensional finite element model is established to analyze the loading test, and a Genetic Algorithm-Backpropagation Neural Network (GA-BPNN) model is employed for the back-analysis of soil parameters. The analysis of the monitoring data reveals that the cumulative settlement initially exhibits an uplift followed by settlement, while lateral displacement progressively decreases, with the influence range of the load extending to approximately 108 m. Sensitivity analysis identifies the internal friction angle φ and E ref oed of the 2-1A mud layer as the most significant parameters influencing horizontal displacement. The back analysis shows good agreement with the monitoring data, indicating that the model’s predictions align well with the observed results. The in-situ loading tests and back analysis results offer valuable insights into the deformation behavior of soils under surcharge loading and provide a robust framework for model calibration, ultimately contributing to the safety and stability of similar infrastructure projects.